Role of a redox-based methylation switch in mRNA life cycle ( pre- & post- transcriptional maturation) and protein turnover : Implications in neurological disorders - TRIVEDI, MALAV S.; Deth, Richard C. (Frontiers in Neuroscience, 2012)
Homeostatic synaptic scaling in response to neuronal stimulus or activation, as well as due to changes in cellular niche, is an important phenomenon for memory consolidation, retrieval, and other similar cognitive functions. Neurological disorders and cognitive disabilities in autism, Rett syndrome, schizophrenia, dementia etc., are strongly correlated to alterations in protein expression (both synaptic and cytoplasmic). This correlation suggests that efficient temporal regulation of synaptic protein expression is important for synaptic plasticity. In addition, equilibrium between mRNA processing, protein translation and protein turnover is a critical sensor/trigger for recording synaptic information, normal cognition and behavior. Thus a regulatory switch, controlling the lifespan, maturation and processing of mRNA, might influence cognition and adaptive behavior. Here, we propose a two part novel hypothesis that methylation might act as this suggested coordinating switch to critically regulate mRNA maturation at 1.The pre-transcription level, by regulating precursor-RNA (pre-RNA) processing into mRNA, via other non-coding RNAs and their influence on splicing phenomenon, and 2. the post-transcription level by modulating the regulatory functions of ribonucleoproteins (RNP) and RNA binding proteins (RNABP) in mRNA translation, dendritic translocation as well as protein synthesis and synaptic turnover. DNA methylation changes are well recognized and highly correlated to gene expression levels as well as, learning and memory; however, RNA methylation changes are recently characterized and yet their functional implications are not established. This review article provides some insight on the intriguing consequences of changes in methylation levels on mRNA life-cycle. We also suggest that, since methylation is under the control of glutathione antioxidant levels, the redox status of neurons might be the central regulatory switch for methylation-based changes in mRNA cycle